Poedji Rochjati Score Card as Media for Preconception Counseling - Simanungkalit, Naomy; Handayani, Samsriyaningsih; Akbar, Muhammad Ilham Aldika (Folia Medica Indonesiana, 2021)
Highlight:• The PCC counseling effect using Poedji Rochjati Score Card (PRSC) on premarital knowledge about high-risk pregnancies was studied. • PRSC for preconception counseling is effective for women to improve knowledge about high-isk pregnancy. Abstract: Preconception care (PCC) is a health approach that includes promotive and preventive activities to detect risk factors and interventions carried out to expectant mothers by considering biological, behavioral, and social aspects that affect their health. This study studied the effect of PCC counseling using Poedji Rochjati Score Card (PRSC) on premarital knowledge about high-risk pregnancies. This study was quasi-experimental with 52 respondents divided into 4 groups, namely intervention and control groups, 2 groups with partners, and 2 groups without partners that were chosen through total sampling by applying inclusion and exclusion criteria. Knowledge was measured using pretest and posttest questionnaires. The intervention given was in the form of counseling using PRSC for ± 20 minutes. There were differences in knowledge between the intervention and control group among respondents without partners. Preconception counseling using PRSC was effective for women attending premarital health checks. Applying PRSC as media for counseling could improve knowledge in high-risk pregnancy that could be avoided.